A complexity perspective on leadership and change in the post-merger integration process. (16th February 2009) - Lauser, Barbel; Peters, Mike
After 30 years of research in mergers and acquisitions and advances in the research of post-merger integration (PMI) processes, the outcome of a merger remains hardly predicable. Traditional leadership and change theories have not succeeded in fully explaining PMI processes and therefore new theories are needed. This article offers new insights into the integration and change processes by looking at the merged organisation as a complex adaptive system (CAS). It discusses characteristics of CAS and applies them to PMI, and questions pure cause-and-effect relationships by interpreting change processes as sometimes non-linear, unpredictable, with various feedback mechanisms. In addition, the article summarises new leadership theories emerging from a complexity perspective which might contribute to a better understanding of the PMI process. It concludes by advocating that for a successful integration both, traditional and complexity leadership is needed.